2020
DOI: 10.1242/bio.052993
|View full text |Cite
|
Sign up to set email alerts
|

Site-1 protease ablation in the osterix-lineage in mice results in bone marrow neutrophilia and hematopoietic stem cell alterations

Abstract: Site-1 protease (S1P) ablation in the osterix-lineage in mice drastically reduces bone development and downregulates bone marrow-derived skeletal stem cells. Here we show that these mice also suffer from spina bifida occulta with a characteristic lack of bone fusion in the posterior neural arches. Molecular analysis of bone marrow-derived non-red blood cell cells, via single-cell RNA-Seq and protein mass spectrometry, demonstrate that these mice have a much-altered bone marrow with a significant increase in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…The results of qPCR analysis showed that 9 upregulated genes, Pdzk1 , Vpreb1a , Cd72 , Igll1 , Tnfrsf19 , Gas6 , Zdhhc2 , Igfbp4 , and Hdac7, were significantly increased, and 10 downregulated genes, Dhcr24 , Padi4 , Gsr , Clec4d , Lilrb4a , Clec4e , Fcgr4 , Stfa2 , Olfm4 , and Cxcr1, were significantly decreased in Mx1;TβRI CA compared to the WT group ( Figure 4 A,B). The functions of these 19 DEGs are briefly described in Supplementary Tables S1 and S2 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of qPCR analysis showed that 9 upregulated genes, Pdzk1 , Vpreb1a , Cd72 , Igll1 , Tnfrsf19 , Gas6 , Zdhhc2 , Igfbp4 , and Hdac7, were significantly increased, and 10 downregulated genes, Dhcr24 , Padi4 , Gsr , Clec4d , Lilrb4a , Clec4e , Fcgr4 , Stfa2 , Olfm4 , and Cxcr1, were significantly decreased in Mx1;TβRI CA compared to the WT group ( Figure 4 A,B). The functions of these 19 DEGs are briefly described in Supplementary Tables S1 and S2 [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…At least six mouse tissues per group were used for the experiment. (Patra et al, 2020). Cells were incubated at 37 C under normoxic conditions and the medium was changed every 3 days until the cells had matured to form adipocytes (Day 8).…”
Section: Hematoxylin-eosin (He) Stainingmentioning
confidence: 99%